Parametric investigation of a chilled water district cooling unit using mono and hybrid nanofluids - Eric C. Okonkwo (14151060) (2021)
This study presents a novel parametric investigation into the performance of a district cooling system using mono (Al2O3 and TiO2) and hybrid (Al2O3–TiO2) nanoparticles in the base fluids of water and ethylene–glycol water (EG-water) at a 20:80 ratio. The study analyses the effect of variables such as secondary fluid flow rate, evaporator and inlet temperatures, nanoparticle concentration, and air flowrate on the COP, total electrical energy consumption, and design of the district cooling unit. The analysis is performed with a thermal model developed and validated using operations data obtained from the McQuay chilled water HVAC unit operating in one of the facility plants at the Education City campus. The results of the study show that the use of nanofluids increased the overall heat transfer coefficient in the system by 6.6% when using Al2O3–TiO2/water nanofluids. The use of nanofluids in the evaporator also led to an average reduction of 23.3% in the total work input to the system and improved the COP of the system by 21.8%, 20.8% and 21.6% for Al2O3–TiO2/water, Al2O3/water, and TiO2/water nanofluids, respectively. Finally, an enhancement of 21.6% in COP was recorded for Al2O3–TiO2/EG-water nanofluids at a 5% nanoparticle volume concentration. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-021-98754-7